(untitled) (CIPEEX, 2024)
INFORMATION TECHNOLOGY (IT) IN THE BUSINESS CONTEXT CAN BE CHARACTERIZED AS THE USE OF COMPUTING RESOURCES AND TECHNIQUES FOR OBTAINING, PROCESSING AND ORGANIZING DATA, WITH THE MAIN PURPOSE OF AUTOMATING PROCESSES, DECISION MAKING IS DONE IN AN ASSERTIVE WAY. BEING INCREASINGLY PRESENT WITHIN ORGANIZATIONS, IT IS REMARKABLE THAT BRAZILIAN MICRO AND SMALL ENTERPRISES (MSES) STILL FACE SIGNIFICANT SHORTAGES IN RELATION TO THE ADOPTION OF COMPUTERIZED SYSTEMS. THUS, THE OBJECTIVE IS TO ANALYZE THE IMPORTANCE OF TECHNOLOGICAL INNOVATION IN THE BUSINESS CONTEXT, SEEKING TO IDENTIFY THE REASONS BEHIND ITS LIMITED PRESENCE IN MSES. THEREFORE, A BIBLIOGRAPHIC RESEARCH OF THE NARRATIVE TYPE WAS CARRIED OUT IN ARTICLES PUBLISHED IN PORTUGUESE BETWEEN THE YEARS 2019 TO 2023, TAKEN FROM THE DATABASES GOOGLE SCHOLAR, SCIELO, AND JOURNAL CAPES. AFTER THE ANALYSIS IT WAS EVIDENCED THAT THE COMPANIES THAT INVEST IN INNOVATION AND TECHNOLOGY ARE OF FUNDAMENTAL IMPORTANCE TO THE ECONOMY OF THE COUNTRY, HOWEVER MOST OF THE MSES HAVE RESTRICTED ACCESS TO THIS MODERNIZATION AFFECTING THE GROWTH OF THEM, TECHNOLOGICAL FACTORS ARE RESPONSIBLE FOR CONTINUOUS ADAPTATIONS OF THE CORPORATE STRATEGIC POSTURE, ALSO INFLUENCING THE TACTICAL AND OPERATIONAL LEVEL OF THE ORGANIZATION. IT WAS FURTHER CONFIRMED THAT THERE IS AN IMMENSE DIFFICULTY IN THE HANDLING CAPACITY OF IT IN MSES, BECAUSE THERE IS A GREATER LIMITATION WITHIN THESE MODALITIES ABOUT THEIR COMPLEXITY. THROUGH THE FACTS PRESENTED, THE INFORMATION TECHNOLOGY FOR MSES IS A RESOURCE DIFFICULT TO ACCESS, BECAUSE IT HAS A CONSIDERABLE HIGH COST AND A DIFFICULTY TO ADAPT TO ITS USE, THUS, IN ORDER FOR THE FEASIBILITY OF IMPLEMENTING AN INFORMATION TECHNOLOGY TO BE SUCCESSFUL IN MICRO AND SMALL COMPANIES IT IS NECESSARY THAT THEY ARE AWARE THAT THE BENEFITS WILL COME IN THE MEDIUM AND LONG TERM, IN ADDITION, IT IS SEEN THAT THE USE OF SUCH TOOLS PROVIDE THEIR USERS QUICK RESPONSES IN THE SIMPLEST AND MOST ECONOMICALLY POSSIBLE WAY, CONSEQUENTLY IMPROVING THE CHANCES OF GROWTH AND BUSINESS DEVELOPMENT, AND ABROAD ENABLING IMPROVEMENTS TO THE BRAZILIAN ECONOMY.